KEDUDUKAN JANDA NYEROD DALAM KELUARGA TRI WANGSA DI PULAU LOMBOK - Desak Made Yoniartini (Institut Agama Hindu Negeri Gde Pudja Mataram, 2020)
This article aimed at finding out how the position of the widow in tri wangsa family in Lombok island. This article used conflict and balance theory. The findings of the article namely nyerod marriage (perkawinan nyerod) was considered as a taboo thing in the past, but now it does not become any problem anymore. A woman who has married by using way of nyerod, and she becomes a widow and he will return home to her parents, she will be accepted well by her parents based on the reasons of brotherhood and humanity. Even though she has been accepted well, but in the reality she/the widow does not have the same right as when she has not married yet. Even though she has performed mulih bajang/mulih daa ceremony, but she have not been fully accepted by her family, such as she does not have a right to accept inheritance, and she will not receive respect at the death ceremony